Influence of Equal Channel Angular Pressing Technique on Mechanical Properties, Corrosion Resistance, and Microstructural Behavior of Al-Alloy 5083 - Mishra, Vishwesh; Singhal, Piyush (Recent Patents on Mechanical Engineering, 2025)
Introduction During severe plastic deformation (SPD) processing, aluminum alloys exhibit moderate strength and ductility. Nevertheless, the materials' ductility, as determined by tensile testing, does not accurately represent their capacity for plastic deformation. After the tensile test, its material, aluminum alloy 5083, was observed to be super ductile. Methods The results of a more thorough plasticity analysis—applied for the first time to material following SPD processing—are presented in this paper. The aluminum alloy 5083 is examined in the patent both before and after equal channel angular pressing (ECAP). A highly effective aluminum alloy 5083 specimen preparation was suggested. Under heated temperatures, the process involves severe plastic deformation. Optical microscopy and scanning electron microscopy (SEM) were used for micro-structural research in order to look at the distribution of second-phase particles and the evolution of grain structure. Furthermore, Vickers micro-hardness testing was utilized to assess the mechanical characteristics of the alloy after processing. The outcomes showed that after ECAP processing, there was a significant decrease in grain size and an increase in micro-hardness. Results Additionally, the production of a finer microstructure with a more uniform distribution of strengthening precipitates was clarified by electron microscopy (SEM). The micro-structural evolution and mechanical behavior of aluminum alloy 5083 under ECAP are well-explained in this patent, which may lead to improved performance in structural applications. This method can be used to forecast fractures in plastic deformation processes and estimate the final plasticity of the materials for various stress-strain states after ECAP processing, as well as the mechanical properties discussed. Conclusion Due to its unique mechanical qualities, aluminum alloy 5083 shows great potential in a variety of structural applications. The effects of Equal Channel Angular Pressing (ECAP) on the hardness and microstructure of aluminum alloy 5083 were examined in this patent work.
Keywords: wear